DCZ0801, a novel compound, induces cell apoptosis and cell cycle arrest via MAPK pathway in multiple myeloma. (4th April 2019) - Zhang, Ting; Li, Bo; Feng, Qilin; Xu, Zhijian; Huang, Cheng; Wu, Huiqun; Chen, Zhangbo; Hu, Liangning; Gao, Lu; Liu, Peng; Yang, Guang; Zhang, Hui; et al.
Abstract: Multiple myeloma (MM) is a refractory malignant hematological malignancy, and many therapeutic strategies have been developed to cure patients with MM. DCZ0801 is a compound that consists of oxophenamide and pterostilbene. The role of these compounds in hematological cancers such as MM has yet to be studied. In this study, we explored the potential mechanism of DCZ0801 action, its anti-tumor activity both in vitro and in vivo on MM. This study was carried out via cell cycle proliferation assay, apoptotic analysis, western blot analysis, and examination of xenotransplantation model of tumors. The in vitro studies revealed that DCZ0801 could inhibit cell proliferation and induce apoptosis by regulating both caspase-dependent and mitogen-activated protein kinase signaling pathways, inducing S-phase arrest of the cell cycle related to downregulation of CDK2, cyclin-A2, and CDC25A protein expression. The in vivo studies showed that DCZ0801 could significantly reduce the size of the tumors in nude mice. Our results demonstrated that DCZ0801 may emerge as the new therapeutic option for the patient with MM.